A new proposal for design of laterally unsupported monosymmetric steel I-section beams at elevated temperature. (April 2022) - Suman, Saurabh; Samanta, Avik
Abstract: Fire causes one of the worst hazardous situations to structures. With the increase in temperature, there is a rapid decrease in steel material properties, which eventually leads to a reduction in the flexural capacity of the beam members. Lateral-torsional buckling (LTB) may predominate the design strength predictions for laterally unsupported beams. A rapid decrease in the capacity at high-temperature may result in premature failure of beams. Past studies have focused on predicting LTB design curves using a single equation, varying with reduction factors at elevated temperatures. These curves may result in a very conservative design that might change with the loading patterns and can sometimes predict unsafe design strengths. The present manuscript carries out a parametric study using a validated numerical model. The robust computational software ABAQUS is used for simulating a total of 2100 elastic and inelastic beam models. A new proposal is recommended for predicting the design capacity of monosymmetric I-section beams for the uniform moment, moment gradients, point load at mid-span, and uniformly distributed load (UDL) at elevated temperature. Further, a statistical study is conducted to ascertain the accuracy of the present proposal. The resulted data is also compared with the available literature. The results show that the current proposal provides economical, and safe predictions.